Concentration-dependent antibacterial activity of Ruellia tuberosa L. leaf ethanol extract against Propionibacterium acnes ATCC 6919 - Yani, Indri; Hamidu, La; Meiliana, Made Laksmi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Rising antibiotic resistance in Propionibacterium acnes necessitates alternative anti-acne agents. Ruellia tuberosa L. (Acanthaceae) possesses documented antibacterial potential, yet its activity against P. acnes remains unevaluated. This study investigated the concentration-dependent antibacterial activity of R. tuberosa leaf ethanol extract against P. acnes ATCC 6919. Leaves were extracted by maceration using 96% ethanol. Phytochemical classes were identified by thin-layer chromatography. Antibacterial activity was assessed using the Kirby-Bauer disc diffusion method in triplicate (n = 3) at concentrations of 15%, 20%, 25%, 30%, and 35% (w/v), with 0.1% clindamycin and distilled water as positive and negative controls, respectively. Data were analyzed by one-way ANOVA with Tukey's HSD post-hoc test. TLC confirmed alkaloids, flavonoids, tannins, saponins, and terpenoids. Inhibition zones increased from 5.00 ± 1.30 mm (15%, weak) to 11.82 ± 0.84 mm (35%, strong), compared to 22.05 ± 0.27 mm for clindamycin. Significant differences were detected among all groups (p < 0.0001). The 30% concentration was the lowest to achieve strong inhibitory activity, with no significant advantage conferred by increasing to 35%. R. tuberosa leaf ethanol extract exhibits concentration-dependent antibacterial activity against P. acnes, with 30% identified as the optimal concentration, warranting further investigation for botanical anti-acne formulation development.